Peran Komnas HAM dalam Pencegahan dan Penanganan Pelanggaran Hak Asasi Manusia - Iswani. S, Rina; Yanti, Jeli; Karera, Vaula (GLOBAL SCIENTS PUBLISHER, 2025)
The enforcement of human rights (HAM) in Indonesia faces significant challenges in the digital era, where advances in information technology have added new dimensions to violations such as intimidation on social media and cybercrime. Although the National Commission on Human Rights (Komnas HAM) plays a central role in investigating gross and non-gross human rights violations, its limited authority, particularly in investigation and prosecution, hinders the effectiveness of case resolution. This study aims to evaluate the influence of authority, human resource capacity, and institutional coordination on optimal and independent human rights protection. Normative juridical methods were used, analyzing official documents, literature, and investigative reports. The results indicate the need for regulatory reforms that grant Komnas HAM broader legal authority, increase technical capacity, and strengthen synergy with law enforcement. Public human rights education is also considered crucial in building a culture of respect for human rights. In conclusion, strengthening the authority and capacity of Komnas HAM, coupled with inter-institutional collaboration, will enhance fair, transparent, and sustainable human rights protection and enforcement in Indonesia.